Computer Assisted Learning Teacher Training Methodology and Evaluation of a Seminar for Language Teachers - Kreutzer, Martin; Neunzig, Wilhelm (CALICO journal, 1996)
Commissioned by the Department of Education, Culture and Sport of the Autonomous Government of the Canary Islands, the co-authors of this article describe a methodology for teaching training seminars designed to reconsider and define the validity of the design of CALL exercises developed by teachers of the subject and aimed at solving specific problems presented by their own students. A three-stage system of evaluation was used to collect empirical data in support of the validity of the initial hypothesis.